Evaluation of the impact of enhanced primary health care intervention programme in Malaysia: a repeat cross-sectional pre-post quasi experimental study - Muhammad Fadhli Mohd Yusoff; Thamil Arasu Saminathan; Miaw Yn, Jane Ling; Wan Shakira Rodzlan Hasani; Nur Liana Ab Majid; Halizah Mat Rifin; Tania Gayle Robert Lourdes; Hasimah Ismail; Suhaila Abdul Ghaffar; Mohd Hasnan Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Non-communicable diseases (NCD) lead to substantial mortality and morbidity worldwide. Malaysia is currently experiencing an epidemic of NCDs. This paper aims to evaluate the effectiveness of the Enhanced Primary Health Care (EnPHC) intervention in reducing the prevalence of undiagnosed diabetes, undiagnosed hypertension, and undiagnosed hypercholesterolemia as well as NCD risk factors in the population after about one year of intervention. This is a repeat cross-sectional pre-post quasi-experimental study comparing intervention and control groups. The target population included adults aged 30 years and above living within the 40 selected clinics' catchment areas for at least six months. Data were collected using face-to-face interviews and clinical assessments. A difference-in-difference (DID) analysis was used to determine the effect of the EnPHC intervention. The percentage of the population screened for diabetes mellitus, hypertension, and hypercholesterolemia increased from the baseline status by 8.7%, 9.9%, and 9.2%, respectively. The prevalence of undiagnosed diabetes mellitus and hypercholesterolemia decreased from the baseline status by 17.6% and 13.7% compared to the control group. However, the EnPHC intervention did not affect the prevalence of overweight, obesity and smoking. The EnPHC intervention contributed to the reduction in the prevalence of undiagnosed NCDs. A more extended period of intervention would be required to show the effect on NCD risk factors. Further strengthening of the intervention would be needed for implementation in other localities.